2019
DOI: 10.1039/c8ra09193e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blending sequences and molecular structures of the compatibilizers on the morphology and properties of PLLA/ABS blends

Abstract: The morphology and properties of compatibilized PLLA/ABS blends can be optimized by using appropriate compatibilizers and blending sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This effect will be the strongest when the graft groups are concentrated in one region of the compatibilizer. 13,14 Maleic anhydride as the functional graft moiety can interact with PET and is often used as it does not easily homopolymerize and has a better thermal stability compared to other graft moieties. [15][16][17][18][19] The more reactive glycidyl methacrylate graft group was not included in the research, even though it is more suitable for PET covalent bonding since it has a higher tendency for homogenous polymerization during the grafting process.…”
Section: Introductionmentioning
confidence: 99%
“…This effect will be the strongest when the graft groups are concentrated in one region of the compatibilizer. 13,14 Maleic anhydride as the functional graft moiety can interact with PET and is often used as it does not easily homopolymerize and has a better thermal stability compared to other graft moieties. [15][16][17][18][19] The more reactive glycidyl methacrylate graft group was not included in the research, even though it is more suitable for PET covalent bonding since it has a higher tendency for homogenous polymerization during the grafting process.…”
Section: Introductionmentioning
confidence: 99%
“…Small amount of compound is added to multicomponent polymer systems as a compatibilizer which is expected to chemically or physically interact with the polymer components and then to improve the interfacial strength and decrease the size of the dispersion phase. , Thus, a series of molecular structures like block, graft, and comb polymers have been designed and applied as compatibilizers in immiscible polymer blends. The parameters of their molecular structures like block length in block polymers and number and length of side chains in graft and comb polymers are optimized to manipulate the compatibilizers to be enriched at the matrix/domain boundary. However, it is difficult to identify the location of the compatibilizers in the polymer blends owing to its small amount, which is usually less than a few weight percent.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that PLLA/COC10-nHA had enhanced mechanical properties as compared to the PLLA/nHA. These results lead to the assumption that COC chains were not only reinforcing the polymer matrix, but were also involved in the better dispersion of nHA in polymer matrix as corroborated by SEM [43].…”
Section: Mechanical Properties Of Nanocompositesmentioning
confidence: 53%